Active KTaO3 hybrid terahertz metamaterial - Liang Wu (Nature Portfolio, 2017)
Abstract The dielectric properties of an active KTaO3 hybrid metamaterial structure and its tunability under external electric fields are investigated at room temperature by means of terahertz time-domain spectroscopy. Application of the electric field leads to an appreciable tuning of the dielectric loss, which is up to 17%. Meanwhile, the refractive index also changes appreciably. These findings are attributed to the internal space charge field in the crystal caused by the excited free carriers.